2017
DOI: 10.1177/000313481708301123
|View full text |Cite
|
Sign up to set email alerts
|

Hypoalbuminemia and Clinical Outcomes: What is the Mechanism behind the Relationship?

Abstract: Albumin has a number of important physiologic functions, which include maintaining oncotic pressure, transporting various agents (fatty acids, bile acids, cholesterol, metal ions, and drugs), scavenging free oxygen radicals, acting as an antioxidant, and exerting an antiplatelet effect. Hypoalbuminemia in adults, defined by an intravascular albumin level of <3.5 g/dL, is associated with poor postoperative outcomes in patients undergoing surgical intervention. Although the relationship of hypoalbuminemia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
126
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 182 publications
(147 citation statements)
references
References 52 publications
1
126
1
6
Order By: Relevance
“…In addition, the use of MVR was not associated with worse overall or severe morbidity on multivariate analyses. Instead, we observed that other variables typically associated with a greater risk of surgical complications, such as malnutrition (hypoalbuminemia) and tumor size >10 cm, were significant predictors of surgical complications following RPS resection in our analysis. Although retrospective in nature, these data provide further evidence suggesting that MVR for RPS can be performed with acceptable morbidity and mortality, including at a cross‐section of NSQIP hospitals.…”
Section: Discussioncontrasting
confidence: 71%
“…In addition, the use of MVR was not associated with worse overall or severe morbidity on multivariate analyses. Instead, we observed that other variables typically associated with a greater risk of surgical complications, such as malnutrition (hypoalbuminemia) and tumor size >10 cm, were significant predictors of surgical complications following RPS resection in our analysis. Although retrospective in nature, these data provide further evidence suggesting that MVR for RPS can be performed with acceptable morbidity and mortality, including at a cross‐section of NSQIP hospitals.…”
Section: Discussioncontrasting
confidence: 71%
“…Low albumin in oncology patients is often due to increased capillary membrane permeability, lack of protein intake, and systemic inflammatory state (negative acute phase protein). [26][27][28] Albumin is responsible for physiologic functions such as oncotic pressure maintenance and fatty acid, toxin, and drug transport. 25,26 However, it is unclear whether low albumin is the cause or indicator of systemic process associated with poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology involves various cytogenetic changes with gene mutations with widespread hypomethylations in the genome. 1,2 The clinical manifestations result from various combination of cytopenias-anaemias, leucopenias and thrombo-cytopenias. Diagnosis involves peripheral blood examination and bone marrow examinations showing a variety of changes in the different subtypes of myelodysplastic syndrome ranging from cytopenias to hyperproliferation with dysplasias and variable amount of blast cells.…”
mentioning
confidence: 99%
“…2,3 The mechanism postulated for low serum albumin in inflammation is by various cytokines like TNF, IL-6, causing high vascular permeability, high albumin degradation and TNF alpha mediated downregulation of albumin gene transcription. 2 Decrease in serum albumin in various medical conditions by as low as 10 g/L causes mortality to increase by 137% and morbidity by 89%. The exact mechanism that causes low serum albumin to cause high mortality and morbidity is unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation